Fenoterol, a β2-adrenoceptor agonist, inhibits LPS-induced membrane-bound CD14, TLR4/CD14 complex, and inflammatory cytokines production through β-arrestin-2 in THP-1 cell line - Wang Wei; Xu Ming; Zhang You-yi; He Bei (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the molecular mechanism and signaling pathway by which fenoterol, a β2-adrenergic receptor (β2-AR) agonist, produces anti-inflammatory effects. Methods: THP-1, a monocytic cell line, was used to explore the mechanism of β2-AR stimulation in LPS-induced secretion of inflammatory cytokines and changes of toll-like receptors (TLRs). We labeled TLR4 and CD14 using monoclonal anti-TLR4 PE-conjugated and anti-CD14 FITC-conjugated antibodies in THP-1 cells stimulated by β2-AR in the presence or absence of lipopolysaccharide (LPS) and small, interfering RNA (siRNA)-mediated knockdown of β-arrestin-2, and then analyzed their changes in distribution by flow cytometry, Western blotting and confocal analysis. Results: LPS-induced membrane-bound CD14, TLR4/CD14 complex levels and elevation of inflammatory cytokines were all significantly reduced by pre-incubation of fenoterol (P